Anatase TiO(2) nanotube powder film with high crystallinity for enhanced photocatalytic performance - Lin, Jia (Nanoscale Res Lett, 2015)
We report on the synthesis of TiO(2) nanotube (NT) powders using anodic oxidation and ultrasonication. Compared to free-standing NT array films, the powder-type NTs can be easily fabricated in a cost-effective way. Particularly, without the substrate effect arising from underlying Ti metals, highly crystallized NT powders with intact tube structures and pure anatase phase can be obtained using high-temperature heat treatment. The application of NTs with different crystallinity for the photocatalytic decomposition of methylene blue (MB) was then demonstrated. The results showed that with increasing annealing temperature, the photocatalytic decomposition rate was gradually enhanced, and the NT powder electrode annealed at 650°C showed the highest photoactivity. Compared to typical NTs annealed at 450°C, the rate constant increased by 2.7-fold, although the surface area was 21% lower. These findings indicate that the better photocatalytic activity was due to the significantly improved crystallinity of anatase anodic NTs in powder form, resulting in a low density of crystalline defects. This simple and efficient approach is applicable for scaled-up water purification and other light utilization applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s11671-015-0814-6) contains supplementary material, which is available to authorized users.